Postsynthetic functionalization of glycodendrons at the focal point - Lindhorst, Thisbe K.; Elsner, Katharina (Beilstein Journal of Organic Chemistry, 2014)
Glycodendrons are multivalent glycoconjugates bearing an orthogonal functional group at the focal point of the molecule. This allows for their postsynthetic elaboration to achieve amphiphilic glycolipid mimetics, for example, which eventually can be applied in biology, biophysics, or material science. Here, postsynthetic modification of di- and tetravalent polyether glycodendrons has been explored using etherification, thiol-ene reaction and in particular olefin cross metathesis.
Keywords: amphiphilic glycomimetics; cross metathesis; glycodendrons; multivalent glycoconjugates; multivalent glycosystems